Legal Technologies of Creation of Legal Documents - I. N. Senin (Сибирское юридическое обозрение)
The presented article contains theoretical material examining one of major directions of practical jurisprudence, touching a legal technique. Modern legal technique is nothing more than a set of technologies for creating legal documents in the process of implementing a variety of legal activities that require documentary design. The article deals with issues related to types of legal technique, their nature, ways of implementation are analyzed.